Jawabanmu

2014-02-11T20:36:12+07:00
F(x)=a+bx

f(6)= a+6b= -13
f(-2)= a-2b=11
---------------------- -
            8b=-24
             b = -3
f(6)=a + 6(-3)= -13
       a-18=-13
         a = 5

f(3) = a+3b
     = 5+3(-3)
     = -4
f(x)= a+bx
[f(6)= a+6b = -13] – [f(-2)= a-2b= 11]
8b=-24
b= -24:8
b= -3

f(-2)= a + (-2*-3) = 11
a+6=11
a= 11-6
a=5

f(3)=a + bx
f(3)= 5 + (-3*3)
f(3)= 5+(-9) = -4
2014-02-11T20:36:41+07:00
F(x) = a + bx
(f(6) = a+6b = -13) - (f(-2) = a+-2b = 11)
8b = -24
b = -24 : 8
b = -3
a+6b= -13
a+6*-3= -13
a=-13+18
a= 5
f(3) = a+bx =
     = 5+ -3.3 =
     = 5 + -9
     = -4